Investigation of the genotoxicity of digested titanium dioxide nanomaterials in human intestinal cells - Vieira, Adriana (2022)
Funding: This work was funded by national funds through the FCT - Foundation for Science and Technology, I.P., under the project PTDC/SAUPUB/29481/2017. Research co-funded by UIDB/00009/2020; UIDP/ 00009/2020 (Centre for Toxicogenomics and Human Health – ToxOmics, FCT- Foundation for Science and Technology). NV holds a FCT PhD Scholarship grant (2020.07168.BD). iMed.ULisboa (UIDB/04138/ 2020 and UIDP/04138/2020) principal investigator grants CEECIND/ 03143/2017 (L. M. Gonçalves). The authors thank all the support from the colleagues Paula Alvito, Carla Martins and Ricardo Assunç˜ ao (Food Safety Department, INSA, Lisbon, Portugal) as well from all INGESTnano team members.